Correlation between nutritional status values based on World Health Organization child growth standard values and serum albumin levels with wound healing: an observational study - Imam Nugroho, Muhammad Adityo; Sjamsudin, Endang; Hadikrishna, Indra (Universitas Padjadjaran, 2026)
Introduction: Cleft lip and/palate (CL±P) is a congenital disorder that affects the orofacial area, and often associated with problems like feeding difficulties, which may lead to poor nutritional status. Management of cleft lip (CL) requires surgical procedures and wound healing process. Factors influencing wound healing include nutritional status and albumin status. The aim of this study was to analyze the correlation between nutritional status values based on World Health Organization child growth standard values and serum albumin levels with wound healing as measured by Healing Index Scale. Method: This study was conducted on 40 patients with unilateral CL±P who underwent palatoplasty procedure. Participants were selected using a non-probability purposive sampling technique. Saliva samples were collected before palatoplasty and on postoperative day 7 to assess albumin levels, while wound healing was evaluated on day 7 using the Healing Index Scale. Data were analyzed using the Spearman rank correlation test. Results: The nutritional status of patients was predominantly normal in both preoperative (75%) and postoperative day 7 (60%) assessments. Wound healing on day 7 showed that most patients were in the good category (72.5%), while 11 patients (27.5%) were classified as poor. Correlation analysis revealed a very weak and non-significant relationship between WHO child growth standard scores and salivary albumin levels, as well as non-significant relationship between WHO CGS nutritional status and the day 7 healing index in patients undergoing palatoplasty. Conclusion: No significant correlation was found between nutritional status, salivary albumin levels, and wound healing outcomes in patients undergoing palatoplasty.